Un herbario de Costa Rica llega a 75 años - Morales, Carlos (Lankesteriana: International Journal on Orchidology, 2015)
The name of one of its founders, Dr. Luis A. Fournier, was given to the Herbarium of the University of Costa Rica (USJ) in December 2005. During 75 years (1931-2006) this herbarium has contributed to the botanical research in Costa Rica. An update of the vascular plant type catalogue of USJ is included here.